A new criterion for critical suspension of nonuniform sediment. Issue 3 (3rd July 2022) - Sun, Zhilin; Sun, Lixia; Gao, Yun; Zheng, Haolei; Xiang, Wengang; Gao, Yimeng
ABSTRACT: As the lower boundary of suspended particles, the critical condition of suspension is an important component in the theory of nonuniform sediment transport and plays a significant role in the numerical computations in the suspended sediment movement. Previous studies on critical suspension are mostly based on Rouse number and Shields number. From the perspective of maximum particle size, this paper conducted research on the critical suspension of nonuniform sediment by flume experiment. A new criterion for critical suspension of nonuniform sediment is proposed according to the concept of maximum particle Reynolds number and analysis of experimental data. Sediments will not be suspended unless the particle Reynolds number is less than or equal to the maximum one related to flow and boundary conditions. A formula, established from experimental data, indicates that the maximum particle Reynolds number is proportional to 3 power of Froude number and 1/5 power of relative roughness. As a new criterion for critical suspension, this formula offers a reasonable description of the physical mechanism for the initial movement of the suspended load. Not only does the proposed formula agree well with laboratory and field data, but it also has its advantages compared with traditional criteria.